New Energy Analytical Results for the Regulation of Underactuated Overhead Cranes: An End-Effector Motion-Based Approach - Sun, Ning; Fang, Yongchun (IEEE transactions on industrial electronics (1982), 2012)
In this paper, we present a novel end-effector (payload) motion-based control development approach for the regulation of underactuated overhead cranes, which is efficient even in the presence of external disturbance and system parameter variations/uncertainties. The control system is elegantly constructed so that the problem of simultaneously regulating the trolley motion and suppressing the payload swing is successfully addressed by stabilizing a newly defined payload motion signal. Specifically, we first couple the actuated trolley motion and the unactuated payload swing via the defined payload motion signal, based on which a new energy storage function is established. Consequently, a payload motion-based control law is constructed straightforwardly, and the equilibrium point of the resulting closed-loop system is proven to be asymptotically stable by Lyapunov techniques and LaSalle's invariance theorem. Unlike traditional energy-based controllers, the proposed control law takes a much simpler structure independent of the system parameters. Both simulation and experimental results are included to demonstrate the superior performance of the proposed control method over some traditional controllers and its robustness against parameter variations, which illuminates the promising practical application potentiality of the designed crane control system.